Holocene Dynamics of Temperate Rainforests in West-Central Patagonia - Iglesias, Virginia; Haberle, Simon G.; Holz, Andrés; Whitlock, Cathy (Frontiers in Ecology and Evolution, 2018)
Analysis of long-term ecosystem dynamics offer insights into the conditions that have led to stability versus rapid change in the past and the importance of disturbance in regulating community composition. In this study, we (1) used lithology, pollen and charcoal data from Mallín Casanova (47°S) to reconstruct the wetland, vegetation and fire history of west-central Patagonia; and (2) compared the records with independent paleoenvironmental and archeological information to assess the effects of past climate and human activity on ecosystem dynamics. Pollen data indicate that Nothofagus-Pilgerodendron forests were established by 9000 cal yr BP. Although the biodiversity of the understory increased between 8480 and 5630 cal yr BP, forests remained relatively unchanged from 9000 to 2000 cal yr BP. The charcoal record registers high fire-episode frequency in the early Holocene followed by low biomass burning between 6500 and 2000 cal yr BP. Covarying trends in charcoal, bog development and Neoglacial advances suggest that climate was the primary driver of these changes. After 2000 cal yr BP, the proxy data indicate (a) increased fire-episode frequency; (b) centennial-scale shifts in bog and forest composition; (c) the emergence of vegetation-fire linkages not recorded in previous times; and (d) paludification in the last 500 years possibly associated with forest loss. Our results therefore suggest that Nothofagus-Pilgerodendron dominance was maintained through much of the Holocene despite long-term changes in climate and fire. Unparalleled fluctuations in local ecosystems during the last two millennia were governed by disturbance-vegetation-hydrology feedbacks likely triggered by greater climate variability and deforestation.